PSYCHOLOGICAL RESEARCH ON THE PROBLEM OF GENDER CHARACTERISTICS OF ADOLESCENT AGGRESSION - Burteshova Aliya Burkhanovna; Quyliyeva Orzigul Rajabboyevna (Galaxy International Interdisciplinary Research Journal, 2022)
Adolescence is a complex period of its own, and aggressive behavior has become a natural condition in most of the representatives of this age group. The article describes the classification of aggressive behavior in adolescence and the possibilities of correction.